LIVING IN EXILE: THE INDONESIAN POLITICAL VICTIMS IN THE NETHERLANDS - Amin Mudzakkir (LIPI Press, 2015)
This paper discusses the experience of Indonesian exiles in the Netherlands. Presented in a chronological order from their departure to foreign countries until the post-Suharto era. This paper shows a strong interaction between international and domestic political battles as the context of their origin. Organized based on interviews and observations of the Indonesian exiles in the Netherlands, in addition to related literature review, this paper points out the effort by the exiles to maintain their nasionalist commitment by creating a counter narrative to Indonesian historiography that neglected them. Keywords: 1965 tragedy, exile, citizenship, nationalism